Effect of 3D Metal on Electrochemical Properties of Sodium Intercalation Cathode P2-NaxMe1/3Mn2/3O2 (M = Co, Ni, or Fe) - Nam Pham Phuong Le; Nguyen Le Thanh Huynh; An Le Bao Phan; Dieu Thi Ngoc Nguyen; Trang Thi Thu Nguyen; Hoang Van Nguyen; Xujian Cui; Akhil Garg; Phung My Loan Le; Man Van Tran (Journal of Chemistry)
This research aims to evaluate the influence of different 3D metals (Fe, Co, and Ni) substituted to Mn on the electrochemical performance of P2-NaxMe1/3Mn2/3O2 material, which was synthesized by the coprecipitation process followed by calcination at high temperature. X-ray diffraction (XRD) results revealed that the synthesized Mn-rich materials possessed a P2-type structure with a negligible amount of oxide impurities. The materials possessed their typical cyclic voltammogram and charge-discharge profiles; indeed, a high reversible redox reaction was obtained by NaxCo1/3Mn2/3O2 sample. Both NaxCo1/3Mn2/3O2 and NaxFe1/3Mn2/3O2 provided a high specific capacity of above 140 mAh·g−1; however, the former showed better cycling performance with 83% capacity retention after 50 cycles at C/10 and high rate capability. Meanwhile, the Ni-sub NaxNi1/3Mn2/3O2 exhibited excellent cycling stability but a low specific capacity of 110 mAh·g−1 and inferior rate capability. The diffusion coefficient of Na+ ions into the structure tended to decrease with a depth of discharge; those values were in the range of 10−10–10−9 cm2·s−1 and 10−11–10−10 cm2·s−1 in the solid solution region and biphasic region, respectively.